Effect of deposition time on structural and electrical properties of AZO thin films deposited by spray pyrolysis / Sofea Nabila Hazmin, Mohamad Hafiz Mamat and Nur Amalina Muhamad - Hazmin, Sofea Nabila; Mamat, Mohamad Hafiz; Muhamad, Nur Amalina (Universiti Teknologi MARA, 2021)
Aluminium zinc oxide (AZO) thin films were deposited by spray pyrolysis method using different deposition time 10 s, 20 s, 30 s, 40 s, 50 s and 60 s. The structural and electrical properties of the AZO thin films were investigated by X-ray diffraction (XRD) and two-point probe system. XRD results reveal that all AZO thin films were polycrystalline with hexagonal wurtzite structure with a preferential oriental in the (101) plane. The crystalline size was calculated from Scherrer's formula were in the range from 31 nm to 44 nm. According to the current-voltage (IV) measurement spectra, the AZO thin films deposited on Teflon substrates with different deposition time had a resistivity of 1.08 x 102 Ωcm to 9.78 x 101 Ωcm along with conductivity in the range of 1.02 x 10-2 Scm-1 to 9.26 x 10-3 Scm-1 .